Burnout syndrome in physicians of three hospitals of Huánuco - Cotrina-Onofre, Yony (2019)
Objective: To determine the number of jobs performed, the specialty and the weekly work hours are associated with the Burnout Syndrome in physicians of the hospitals Essalud II, Hermilio Valdizan Medrano and Materno Infantil Carlos Showing Ferrari de Huánuco -2018. Material and method: Observational, descriptive, cross-sectional study. The study variables were Burnout, the number of jobs performed, the specialty and the weekly work hours. All the specialist doctors of the three hospitals were surveyed, consisting of a total of 150. To determine the frequency of the Burnout syndrome, a survey prepared by Maslach was used. Results: It was found that 4 doctors (2.7%) presented Burnout Syndrome. The 8.7% had a high degree of emotional exhaustion, 10% showed a high degree of depersonalization and 78.7% showed a low degree of personal fulfillment. The bivariate analysis did not find significance in relation to the Burnout Syndrome with the variables. Conclusions: Although no significant association was found between the variables studied in the doctors, it was found that a high percentage of physicians had low personal fulfillment, which shows the demotivation, and at higher risk of developing Burnout syndrome.